Legislative malapportionment and the politicization of Germany's intergovernmental transfer system - Hans Pitlik; Friedrich G. Schneider; Harald Strotmann (Center for Economic Studies and ifo Institute (CESifo), 2005)
Legislative bargaining theory suggests that fiscal transfers among member states of a federation are determined to a substantial degree by political bargaining powers. Malapportionment of the states' population in the legislature is claimed to lead to disproportionally higher benefits to overrepresented states. The present paper analyses empirically the distribution of fiscal transfers in Germany's intergovernmental transfer system over the period 1970-2002. It can be shown that overrepresented states in the upper house receive disproportionate shares of transfers, while malapportionment in the lower house does not seem to matter. We also find empirical evidence that overrepresentation became more important over time.
Keywords: D7; H77; 330; legislative bargaining; overrepresentation; fiscal transfer system; Germany; Finanzausgleich; Föderalismus; Verhandlungstheorie; Verhandlungsmacht; Deutschland